2015
DOI: 10.1177/1751143715605119
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review of drug errors in critical care

Abstract: Medication error is the commonest cause of medical error and the consequences can be grave. This integrative review was undertaken to critically appraise recent literature to further define prevalence, most frequently-implicated drugs and effects on patient morbidity and mortality in the critical care environment. Forty studies were compared revealing a markedly heterogeneous data set with significant variability in reported incidence. There is an important differentiation to be made between medication error (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
0
17
0
3
Order By: Relevance
“…Patients admitted to intensive care units (ICUs) may be more likely to be affected by medication errors (MEs) and preventable adverse drug events (ADEs)/adverse drug reactions than those admitted to other wards [1]. This may be due to factors related to the ICU environment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Patients admitted to intensive care units (ICUs) may be more likely to be affected by medication errors (MEs) and preventable adverse drug events (ADEs)/adverse drug reactions than those admitted to other wards [1]. This may be due to factors related to the ICU environment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Using the trigger adapted for intensive therapy was found a rate of 15.8 ADE/100 medical records, mainly caused by high-alert medications. MacFie et al found that the incidence of ADE in ICU ranged widely, from 1.3 to 21.1 (24) . High-alert medications are named because of the increased risk of causing significant harm to patients as a result of a failure to use them (10) .…”
Section: Discussionmentioning
confidence: 99%
“…These pharmacists were members of the UKCPA Critical Care Group ‘Expert Practice Development Group’ which guides development of clinical pharmacy practice in this specialty in the UK . The Round 1 e‐Delphi questionnaire (Delphi Decision Aid; ©2003, J. Scott Armstrong; last updated: 2/17/2005) was composed of list of 15 interventions or resources that reduce medication errors in critical care areas taken from the literature with the addition of medication safety resources recommended in UK critical care practice . In Round 1, participants were asked to indicate ‘Yes’ or ‘No’ whether they perceived an intervention or resource significantly reduced medication errors and were given the opportunity to add other resources.…”
Section: Methodsmentioning
confidence: 99%
“…The complexity of patient care provided means that multiple interventions are likely to be required to address medication error risks – targeting multiple components of the medication process pathway. A recent integrative review of critical care medication errors highlighted the need for large prospective studies of medication areas in this specialty and interventions to reduce them . As such, it remains unknown, which combinations of resources are most effective in improving medication safety .…”
Section: Introductionmentioning
confidence: 99%